Αύξηση του ενδιαφέροντος για εγγραμματισμό της πολιτιστικής κληρονομιάς μέσω πρωτότυπης εφαρμογής edutainment - Γρηγορίου, Λούκας (My University, 2021)
This research study aims to thoroughly examine and develop an original "Edutainment" application combined with augmented reality, which significantly enhances the literacy of the general public in the fields of Cultural Heritage as well as Social Events in relation to the user’s location. The problem addressed in this research study is the lack of physical attendance and thus the lack of awareness on the existence of Cultural Heritage sites or Social Events. With the exception of sites which are widely popular amongst the general public, there seems to be a great number of sites or landmarks with significant historical content that do not have the corresponding attendance. This is due to several facts such as location, and / or the absence of accessibility and visibility to the public. The same applies to Social Events, since it is not always possible to promptly and collectively inform the general public. Therefore, the purpose of this thesis is to investigate the abovementioned issue through research and design, and to develop a suitable and interesting solution which will have the functionality to collect and project data relevant to Cultural Heritage and Social Events within a user-friendly environment. Using features such as Gamification and Augmented Reality, the application will present elements on these topics through interactive media. It may also include digital or physical reward features to provide an incentive for the use of the application.
Keywords: Augmented Reality; Gamification; Edutainment; Cultural Heritage; Πολιτιστική κληρονομιά; Επαυξημένη πραγματικότητα; Κοινωνικά δρώμενα; Παιχνιδοποίηση